PROCESSES CONTROLLING THE OXYGEN ISOTOPE RATIO OF SOIL CO2: ANALYTIC AND NUMERICAL MODELING - IMPLICATIONS FOR PALEOENVIRONMENTAL CHANGE - Stern L.; Baisden W.T.; Amundson R. (My University, 1999)
The 18O/16O ratio of soil CO2 is important for both global and ecosystem scale budgets of the 18O/16O ratio of atmospheric CO2, as well as for using this ratio as a proxy for the isotopic ratio of soil water. The 18O/16O ratio of soil CO2 reflects that of soil water due to the isotope exchange which occurs during the CO2 hydration reaction. The rate of this isotope exchange reaction strongly influences the oxygen isotope ratio of soil CO2, and may be about two orders of magnitude slower than the isotope exchange reaction between CO2(aq) and water (effective first order rate constant, keff, of 10-4 versus 10-2 s-1 at 25°C). This difference in rate reflects transport across the soil water/soil air interface, which limits the overall rate of reaction. A diffusion-production-reaction model (Hesterberg and Siegenthaler, 1991) suggests that the 18O/16O ratio of soil CO2 at depth deviates from the equilibrium value by ~1-2%% if keff = 10-4 s-1, negating the assumption that soil CO2 is in isotopic equilibrium with soil water. A sensitivity analysis of this model indicates the following factors affect 18O/16O ratio of soil CO2 (in order of decreasing importance): (1) the isotope ratio of soil water; (2) the rate constant of the isotope exchange; (3) soil air-filled pore space and tortuosity. Notably, soil respiration rate has only a minor effect. Advection of soil gas due to wind pumping has a negligible effect on the δ18O value of soil CO2 except in most extreme cases. Likewise, transient effects on the oxygen isotope ratio of soil CO2 due to changes in soil respiration rate are small.